Usage Patterns and Awareness of Mobile Health Applications Among Smartphone Users in Assam (GAIMS Journal of Medical Sciences, 2024)
Background: Mobile health (mHealth) initiatives offer significant potential for enhancing healthcare delivery in Assam, where health infrastructure and workforce are limited.Aims and Objectives: This study aimed to assess the awareness and usage patterns of mHealth applications among smartphone users in Assam.Study Design: Online cross-sectional study. Community-based study among adult smartphone users across various districts in Assam.Methodology: The study involved 327 adult smartphone users selected through two-stage sampling. Data were collected using Google Forms and analyzed using Microsoft Excel and SPSS. Statistics: Frequencies and percentages were calculated to describe the data. Statistical associations were examined using the chi-square test and multiple regression analysis.Results: The study found that 82.6% of participants were aware of mHealth apps, primarily recognizing their use for monitoring physical activities (85.2%) and improving doctor-patient communication (84.7%). Urban residents, males, and those with higher education and longer smartphone usage had significantly higher awareness. Additionally, 87% of users had recently used the internet for health information, with Google being the most utilized source (92.6%), followed by social media (62.7%). However, trust in online health information varied, with only 3.7% expressing absolute trust, with male participants and less-educated individuals showing higher trust levels.Conclusion: The study underscores the growing role of mHealth in Assam, highlighting significant awareness. However, trust in online health information remains a concern. These findings suggest the need for targeted educational initiatives and authentic digital information to maximize the benefits of mHealth technologies.